Iridium(I)NHC-phosphine complex-catalyzed hydrogen generation and storage in aqueous formate/bicarbonate solutions using a flow reactor - Effective response to changes in hydrogen demand. (1st November 2019) - Horváth, Henrietta; Papp, Gábor; Kovács, Henrietta; Kathó, Ágnes; Joó, Ferenc
Abstract: Hydrogen gas generation with an effective response to changing application demands was achieved with the use of a hydrogen storage battery based on aqueous cesium bicarbonate hydrogenation/formate dehydrogenation, homogeneously catalyzed by an Ir(I)N-heterocyclic carbene complex. In this device, the storage solution was circulated through a small volume tubular reactor heated to the required high temperature to allow fast hydrogen evolution while the high volume reservoir was kept at ambient temperature at which no H2 was generated. Merely by the control of the reactor temperature, it was possible to regulate the rate of hydrogen evolution as required. The results also demonstrate the feasibility of homogeneous catalysis for the purpose of hydrogen generation in flow systems. Graphical abstract: Image 1 Highlights: Hydrogen generation was accomplished in a tubular flow reactor. Aqueous Cs-formate was applied as hydrogen storage material. Hydrogen generation was catalyzed by a water-soluble Ir(I)NHC-phosphine complex. The rate of H2 evolution was regulated by the temperature of the reactor. Homogeneous catalysis proved feasible for practical H2 storage and generation.